2014
DOI: 10.1063/1.4881059
|View full text |Cite
|
Sign up to set email alerts
|

Electric double layer transistors with ferroelectric BaTiO3 channels

Abstract: We report the surface conduction of a BaTiO3 thin film using electric double layer transistor (EDLT) structure. A transistor operation was observed at 220 K with an on/off ratio exceeding 105, demonstrating that ionic liquid gating is effective to induce carriers at the surface of ferroelectric materials. Temperature dependence of channel resistance exhibited a metallic behavior down to 150 K. EDLT structure is also fabricated using a commercial BaTiO3 bulk single crystal for comparison, which shows abrupt res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In addition to causing the cation nonstoichiometry of those films, the deviation from the growth window might degrade the crystalline quality and induce defects at the interface between the film and the substrate, resulting in strain relaxation. Ferroelectricity was confirmed by piezoresponse force microscopy (PFM) at room temperature 17) for one of the BaTiO 3 films that was grown at 870 °C and TTIP/Ba = 28 within the stoichiometric growth window clarified in this paper. To perform the PFM measurement, a conducting bottom electrode is necessary.…”
mentioning
confidence: 72%
“…In addition to causing the cation nonstoichiometry of those films, the deviation from the growth window might degrade the crystalline quality and induce defects at the interface between the film and the substrate, resulting in strain relaxation. Ferroelectricity was confirmed by piezoresponse force microscopy (PFM) at room temperature 17) for one of the BaTiO 3 films that was grown at 870 °C and TTIP/Ba = 28 within the stoichiometric growth window clarified in this paper. To perform the PFM measurement, a conducting bottom electrode is necessary.…”
mentioning
confidence: 72%
“…Recently, ionic liquid-gated BaTiO 3 single crystal and thin film for EDLTs have been reported by Kozuka and coworkers [75]. The result demonstrated that the on/off ratio exceeding 10 5 at 220 K and similar metallic behavior of channel resistance was observed in thin film at 150 K, although the insulating behavior below this temperature was recovered.…”
Section: Other Phenomena In Perovskite-based Edltsmentioning
confidence: 86%
“…The films were insulated for x ≤ 0.05 and turned metallic at above x ~ 0.2, which is far above the doping level of the present study. By means of electrostatic carrier doping, BTO single crystalline films 21 and SmTiO 3 /BTO heterostructures 22 have been shown to be conductive. However, the relationship between carrier doping and polarity in BTO remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Metalorganic gas-source (MO) molecular beam epitaxy (MBE) was used for film growth. This method has proven effective for growing high-quality complex oxide thin films 21 , 23 25 . Films grown in this way are free of twin boundaries due to a coherent epitaxy with a biaxial compressive strain from a substrate.…”
Section: Introductionmentioning
confidence: 99%